3D built virtual arctic environment increase vigor through connectedness in older people - Clemente D.; Romano L.; Russo C.; Carrus G.; Panno A. (Scientific Reports, 2024)
While the life expectancy of older people has increased significantly, this is often related to more long-term care in healthcare residences and nursing homes. Staying in these facilities can lead to a reduction in the sense of connection with others and the world around, as well as in vigor, with significant psychophysical repercussions in the long term. Although previous studies have shown that the virtual nature can benefit both, there are no significant studies that have tested its effect in generating these positive outcomes in the older population. Therefore, our study sought to investigate, in a sample of 53 older people in care at a nursing home or healthcare residence, the indirect effect of a 3D built virtual arctic environment (vs. a 3D built virtual urban environment) exposure in virtual reality on vigor through connectedness. Both the virtual scenarios were designed with a first-person view, with no translation around the environment and only in-situ rotation. Results highlighted that exposure to the 3D built virtual arctic environment leads to higher connectedness than the 3D built virtual urban environment, and this, in turn, leads to an increase in vigor. Findings were discussed based on the potential of adopting virtual nature in facilities to improve older people's sense of connectedness and, in turn, improve their well-being.